Halal Tourism in The View of Maslahah Mursalah - Wajdi, Farid; Lubis, Ummi Salamah; Lubis, Hamidah Azzahra (Universitas Muhammadiyah Sumatera Utara, 2023)
Indonesia as a country with a majority Muslim population, takes advantage of great opportunities to further develop its potential in the halal tourism sector. Halal tourism began to develop because of the lifestyle needs of people who like to travel but still maintain sharia rules such as halal food and drinks, as well as sharia concept lodging. Islamic scholars agree that the main sources of Islamic law are the Qur'an and hadith. Other sources (theorems) such as ijma', qiyas, istihsan, mashlahah mursalah are still in dispute, both their existence and their intensity as legal arguments. For this reason, it will be seen how halal tourism is in Maslahah Mursalah's view. This research is a normative research with secondary data sources to be analyzed by descriptive analysis. In Maslahah Mursalah's view, a halal tourism concept can certainly provide the benefit of the world and the hereafter to humans. the concept of halal tourism is something that fulfills some of these principles, halal tourism can help humans to relieve fatigue because of activities that are the benefit of basic human needs, this is included in the Maslahah Dhorurriyah printip with the aim of maintaining religion, soul, mind, offspring and property . In addition, halal tourism in the form of mosques can also be managed so that tourist visitors can still worship while traveling with family